1983
DOI: 10.1002/chin.198350201
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: HR 810, a New Parenteral Cephalosporin with a Broad Antibacterial Spectrum.

Abstract: Durch Alkylierung des Cyclopentanopyridins (II) mit den β‐Lactam‐Derivaten (I) erhält man das Antibioticum (III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The ,B-lactams examined were cefpirome (20) and flomoxef (21), which have strong antimicrobial activities against S. aureus as well as gram-negative bacteria; five other cephalosporins (cefotaxime, moxalactam, cefmetazole, cefotiam, and cefazolin); and two penicillins (penicillin G and methicillin). Interestingly, we found that the activities of some ,-lactamase-stable cephalosporins and methicillin were markedly improved when these drugs were combined with sulbactam but that no such synergy occurred when they were combined with clavulanic acid.…”
mentioning
confidence: 99%
“…The ,B-lactams examined were cefpirome (20) and flomoxef (21), which have strong antimicrobial activities against S. aureus as well as gram-negative bacteria; five other cephalosporins (cefotaxime, moxalactam, cefmetazole, cefotiam, and cefazolin); and two penicillins (penicillin G and methicillin). Interestingly, we found that the activities of some ,-lactamase-stable cephalosporins and methicillin were markedly improved when these drugs were combined with sulbactam but that no such synergy occurred when they were combined with clavulanic acid.…”
mentioning
confidence: 99%
“…Cefpirome (HR 810) is a new cephalo sporin derivative of the third generation with an extremely broad antibacterial spectrum [1], including bacterial strains re sistant to cefotaxime and ceftazidime [2]. The pharmacokinetic behaviour of single doses of cefpirome up to 2.0 g has been in vestigated in earlier studies [3].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli Kl and H. influenzae type b are the two most important gram-negative pathogens isolated from infants and children with bacterial meningitis. Cefpirome has excellent antibacterial activity against these two organisms, with reported MICs for 90% of organisms tested of 0.06 and 0.015 jxg/ml, respectively (1,2,13).…”
Section: Discussionmentioning
confidence: 99%